Inequities in HIV prevention among trans and/or non-binary people: a cross-sectional survey analysis of PrEP and PEP awareness and use in Spain - Sara Moreno-García; Paule González-Recio; Marta Donat; Carlos Iniesta; Cinta Folch; María Alonso-Colón; Juan Miguel Guerras; María José Belza (International Journal for Equity in Health)
Abstract Background HIV continues to be a global public health challenge, especially in transgender and non-binary people (TGNB). Despite the high effectiveness of Pre-Exposure Prophylaxis (PrEP) and Post-Exposure Prophylaxis (PEP) in reducing HIV transmission, their implementation in this population is unknown. This study describes PrEP and PEP awareness, knowledge of how to access, and use and identifies the factors associated among the TGNB population living in Spain. Methods Data from 1468 participants in Transaludes, a national online survey aimed at TGNB people living in Spain, were analysed. The prevalence of awareness, knowledge of how to access both PrEP and PEP through the public healthcare system, and use of each strategy were estimated. Factors associated with awareness and use were analysed using Poisson regressions with robust variance. Results A total of 50.5% were aware of PrEP, 14.7% knew how to access PrEP, 2.8% had used it and 1.6% currently, mostly on a daily regimen. A total of 32.5% were aware of PEP, only 13.2% knew how to access PEP and 1.6% had used it, mostly once. Awareness of both strategies was associated with being a non-binary person assigned male at birth (AMAB) or trans woman, being foreign, having a university degree, having undergone biomedical transition and in the past year, having condomless sex with one partner and having engaged in sex work. Use was associated with being older, living in large cities, and in the past year, having condomless sex with two or more partners, having engaged in sex work, and having an STI diagnosis. Conclusions Awareness of PrEP is moderate, while that of PEP is lower; in both cases, there is a high lack of knowledge about how to access them, and use of both strategies is low. Disparities, particularly among certain subgroups, such as trans men, younger TGNB, those with low educational level and those living in smaller cities, reflect structural inequities in access to both strategies. Targeted and tailored strategies, including campaigns to improve awareness and access to these prevention tools are needed to reduce these gaps within TGNB populations and achieve the goals for ending the HIV epidemic.